2012
DOI: 10.4172/2167-1222.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Early Death of Polytrauma Patients: An Analysis of 696 Patients

Abstract: Polytrauma patients are at high risk to die due to acute physiological deterioration after a high injury load within the first hours. Trauma scores such as ISS, NISS and APACHE II and laboratory parameters were collected at admission. The aim of this study was to evaluate the independent predictors of early death of the polytrauma patient. A total of 696 patients (age 40.8 ± 15.5 years) who had an ISS 17 and were admitted to a trauma center within the first 24 hours after trauma were included into this retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
3
13
1
Order By: Relevance
“…Similar admission lactate levels and statistically significant difference in admission lactate levels between compared groups from the present study were also found in other studies [ 3 , 9 , 15 ]. Lactate was found as a modest predictor of outcome with AUC from 0.69 to 0.73 [ 6 , 9 , 12 , 15 ]. Our data showed better accuracy of lactate as a predictor of mortality with AUC of 0.82.…”
Section: Discussionsupporting
confidence: 92%
“…Similar admission lactate levels and statistically significant difference in admission lactate levels between compared groups from the present study were also found in other studies [ 3 , 9 , 15 ]. Lactate was found as a modest predictor of outcome with AUC from 0.69 to 0.73 [ 6 , 9 , 12 , 15 ]. Our data showed better accuracy of lactate as a predictor of mortality with AUC of 0.82.…”
Section: Discussionsupporting
confidence: 92%
“…SIRS was defined as the presence of two or more of the following criteria: body temperature > 38 °C or < 36 °C, heart rate > 90 bpm, respiratory rate > 20 breaths/min or PaCO 2 < 32 mmHg, and white blood cell count >12,000/µL or <4000/µL. The same criteria apply for the presentation of sepsis, with an additional infectious focus [ 7 , 8 , 9 ]. TRISS includes six physiological and clinical parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Reported predictors from literatures were mainly from developed countries with an established trauma database. 7 Among the reported predictors of death was pH of more than 7.2, body temperature of less than 34°C, blood replacement of more than 4000 mL, total fluid replacement of more than 10 000 mL and blood loss of more than 15 mL/min. Reported predictors for survival from traumatic injuries were presence of a penetrating trauma, spontaneous breathing, avoidance of emergency thoracotomy, Injury Severity Score (ISS) ≤20, packed red blood cell replacement of more than 4000 mL and absence of abdominal vascular injury.…”
Section: Introductionmentioning
confidence: 99%